2020
DOI: 10.1071/ah17228
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic involvement in health education within metropolitan, rural and remote Australia: a narrative review of the literature

Abstract: Objective A growing body of research indicates that paramedics may have a greater role to play in health care service provision, beyond the traditional models of emergency health care. The aim of this study was to identify and synthesise the literature pertaining to the role of paramedic-initiated health education within Australia, with specific consideration of metropolitan, rural and remote contexts. Methods A literature review was undertaken using the Ovid Medline, Cumulative Index to Nursing and Allied He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…This is due to the increasing illness rates, a larger patient population, the stress of dealing with difficult patients, and professionals ageing out of the workforce. [16][17][18] However, secondary school graduates and professionals choosing a second career continue to follow more popular professional routes such as nursing, physical therapy, and public health. 19,20 Although members of the general public need additional time to understand each health discipline's background and operation, the Australian government has continued to establish schemes to alleviate the human resources shortages in the health and social care system.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…This is due to the increasing illness rates, a larger patient population, the stress of dealing with difficult patients, and professionals ageing out of the workforce. [16][17][18] However, secondary school graduates and professionals choosing a second career continue to follow more popular professional routes such as nursing, physical therapy, and public health. 19,20 Although members of the general public need additional time to understand each health discipline's background and operation, the Australian government has continued to establish schemes to alleviate the human resources shortages in the health and social care system.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Universities followed these recommendations and expanded their academic departments and programs. 18 The Bradley Review 12,22 further indicated that overall enrolment at Australian universities would increase significantly due to developments such as improved quality of education and the growing international student population. In the 2020/2021 academic year, according to the Australian Health Practitioner Regulation Agency, 23 universities with more than 60 academic programs in most Australian states (except for Tasmania and the Northern Territory) offered degree programs for bachelor's, master's, and master's (graduate entry) degrees.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Outside the Franco-German EMS model (17), emergency physicians are not routinely dispatched to the large group of patients with undifferentiated chest pain, as patients are more efficiently evaluated by regular ambulance paramedics (27). Improved competency and expanded procedure repertory among paramedics seem promising in improving patient care (28), and telemedicine is helpful to provide expert knowledge to the scene (29). We believe the interdisciplinary cooperation between the in-hospital cardiologist and paramedics could be a The five standard TTE projections, stored as ECG synchronized cineloops on the EchoPac server:…”
Section: Discussionmentioning
confidence: 99%